2021
DOI: 10.1073/pnas.2104219118
|View full text |Cite
|
Sign up to set email alerts
|

Calmodulin extracts the Ras family protein RalA from lipid bilayers by engagement with two membrane-targeting motifs

Abstract: RalA is a small GTPase and a member of the Ras family. This molecular switch is activated downstream of Ras and is widely implicated in tumor formation and growth. Previous work has shown that the ubiquitous Ca2+-sensor calmodulin (CaM) binds to small GTPases such as RalA and K-Ras4B, but a lack of structural information has obscured the functional consequences of these interactions. Here, we have investigated the binding of CaM to RalA and found that CaM interacts exclusively with the C terminus of RalA, whic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(14 citation statements)
references
References 43 publications
2
12
0
Order By: Relevance
“…This is consistent with the slightly weaker binding of lipidated RalB to CaM compared with that of lipidated RalA. [10] Given that we know that HVR engagement is necessary for membrane extraction, it is therefore likely that although CaM can extract RalA from membranes in vivo it cannot do the same for RalB. It has previously been reported that CaM interacts with both RalA and RalB, [11,12] but in these experiments solubilised membrane extracts were used, which exposes the lipid moiety.…”
Section: Rala Versus Ralb Binding To Camsupporting
confidence: 76%
See 4 more Smart Citations
“…This is consistent with the slightly weaker binding of lipidated RalB to CaM compared with that of lipidated RalA. [10] Given that we know that HVR engagement is necessary for membrane extraction, it is therefore likely that although CaM can extract RalA from membranes in vivo it cannot do the same for RalB. It has previously been reported that CaM interacts with both RalA and RalB, [11,12] but in these experiments solubilised membrane extracts were used, which exposes the lipid moiety.…”
Section: Rala Versus Ralb Binding To Camsupporting
confidence: 76%
“…When C-lobe interaction with the HVR is blocked, by the introduction of an RalA L195A/I199A double mutation, extraction from the membrane is ablated. [10] NMR experiments were used to compare binding of non-lipidated peptides corresponding to the RalA and RalB HVR [10] (Figure 1A). The peptides were titrated into 15 N labelled CaM, and HSQC experiments were recorded at each titration point.…”
Section: Rala Versus Ralb Binding To Cammentioning
confidence: 99%
See 3 more Smart Citations